Dampak Budaya Literasi dalam Meningkatkan Minat Baca Siswa Kelas 3 SD Negeri Pujer Baru 2 Kecamatan Maesan Melalui Pemanfaatan Pojok Baca - Ade Nurfadilah (Jurnal Eduakasi dan Penelitian Tindakan Kelas, 2023)
In the National Education System Law No. 20 of 2003 Article 4 paragraph 5 states that education is held by developing a culture of reading, writing, and counting. Therefore, in implementing a literacy culture, schools take advantage of the purpose of reading corners in the classroom by increasing students' reading interest, especially at the elementary school level. This study uses a descriptive type approach. The population of this research is the 6th grade students of SD Negeri Pujer Baru 02 with a sample of 10 people. Data collection was done by giving a reading text from the book he chose when reading 1 to 2 paragraphs, then reading for 10 minutes and reflecting for 5 minutes from the text read. The results of the analysis show that there are some students who have difficulty in reading in grade 3 SD Negeri Pujerbaru 02.